ASSOCIATION OF VENTRICULAR LATE POTENTIALS WITH LEFT VENTRICULAR HYPERTROPHY IN PATIENTS WITH SYSTEMIC ARTERIAL HYPERTENSION: Hypertensive Left Ventricular Hypertrophy - Riaz, Bushra; Majeed, Syed Muhammad Imran; Khan, Muhammad Alamgir (Pakistan Armed Forces Medical Journal, 2016)
Objective: To determine the association of ventricular late potentials with left ventricular hypertrophy in patients with systemic arterial hypertension.Study Design: Cohort retrospective study.Place and Duration of Study: Department of Cardiac Electrophysiology, Armed Forces Institute of Cardiology, Rawalpindi from 11th Nov, 2014 to 10th Nov, 2015.Material and Methods: Sixty four patients with systemic arterial hypertension were divided into two equal groups on the basis of left ventricular hypertrophy. Patients with acute or old myocardial infarction, diabetes mellitus, cerebrovascular accident, heart failure, structural heart disease, bundle branch block and cardiomyopathies were excluded from the study. DMS 300 4L Holter monitors were used to obtain 3 channel signal averaged ECG recording. CardioScan premium luxury software was used for analysis of ventricular late potentials.Results: There were 49 (76.6%) males and 15 females (23.4%) with the mean age of 60 ± 11.83 years. Ventricular late potentials were revealed in 10 (31.3%) out of 32 patients with left ventricular hypertrophy whereas in patients without hypertrophy only 1 (3.1%) patient showed it. Ventricular late potentials were strongly associated with left ventricular hypertrophy (p-value=0.03) and the relative risk of developing ventricular late potentials was 10 times higher in patients with left ventricular hypertrophy as compared to those without left ventricular hypertrophy.Conclusion: Ventricular late potentials were strongly associated with left ventricular hypertrophy.